Analisis Determinan Indeks Pembangunan Manusia di Indonesia Tahun 2019 dengan Spatial Error Model (SEM) - Afifah Sukmawati (Politeknik Statistika STIS, 2022)
The success of a country's development is not only measured by its level of economic growth. UNDP in 1990 explained the importance of human-focused development by introducing a concept known as the Human Development Index (HDI). Based on previous research, the factors that influence the HDI are GRDP per capita (GRDP), the realization of government spending in the health sector (EXPH), and the prevalence of early marriage (KAWN). This study uses spatial regression analysis to analyze the factors that influence the HDI in Indonesia in order to accommodate the spatial effects of the data. The unit of analysis used in this study are 34 provinces in Indonesia. By using the SEM model, it is found that the GRDP and KAWN variables have a significant effect on HDI. The GRDP variable has a positive relationship while the KAWN variable has a negative relationship to HDI. Meanwhile, the EXPH variable has no significant effect on HDI in Indonesia. The SEM model is the best model because it has a smaller AIC value than the OLS model.